2007
DOI: 10.1161/circulationaha.107.184047
|View full text |Cite
|
Sign up to set email alerts
|

Development of Systems of Care for ST-Elevation Myocardial Infarction Patients

Abstract: Central to the development of systems and centers of care for ST-elevation myocardial infarction (STEMI) patients will be the key role played by emergency medical services (EMS) at entry into the system and within the system when emergency interhospital transport is required. Current System of Care Emergency Medical Services System DesignPrehospital EMS systems have 3 major components: emergency medical dispatch, public safety (fire and law enforcement) first response, and EMS ambulance response. Each of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 37 publications
0
27
0
1
Order By: Relevance
“…However, this term remained in the model because previous research has indicated the importance of bundling ECG acquisition and hospital notification together. 6 It is important to recognize that not all of these individual components may be feasible for implementation in any 1 EMS system. Focusing on individual components with an overall design for implementation may prove beneficial for EMS systems attempting to improve STEMI care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this term remained in the model because previous research has indicated the importance of bundling ECG acquisition and hospital notification together. 6 It is important to recognize that not all of these individual components may be feasible for implementation in any 1 EMS system. Focusing on individual components with an overall design for implementation may prove beneficial for EMS systems attempting to improve STEMI care.…”
Section: Discussionmentioning
confidence: 99%
“…These times were grouped together as an expression of the integration of prehospital and in-hospital services, one of the key elements of successful chest pain evaluation centers. 6 With prearrival notification of STEMI patients, the PCI centers in this study prepared the CCL and admitted patients directly to the CCL when possible. In some cases, the CCL was not prepared for patient admission by the time of EMS arrival at the hospital.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 EMT-basic personnel provide basic life support, including first aid, cardiopulmonary resuscitation, oxygen, and early defibrillation. EMT-intermediate and EMTparamedic personnel provide advanced life support, including intubation and intravenous medications.…”
Section: What Training and Maintenance Of Competency Do Ems Providersmentioning
confidence: 99%
“…To improve the prognosis of AMI, it is essential to quickly identify the underlying disease and transport the patient to an appropriate medical institution promptly. While performing the initial treatment, the quick judgment must be made by the emergency rescue team 1,2) . However, sometimes it is difficult to implement the above measures in regions which are in remote locations from a medical institution.…”
Section: Introductionmentioning
confidence: 99%